The Uses of Social Networking Sites (SNS) Towards Social Solidarity / Nur Farah Adibah Rozlan - Rozlan, Nur Farah Adibah
Social solidarity is important to build a good nation, especially for a country with have diversity of ethnics, culture, races and language. Nowadays, majority of the people in Malaysia have social networking sites (SNS) and it becomes a routine to surf the social networking sites every day. Therefore, this is when SNS do their works to instill a strong social solidarity among the people in this country. Social networking sites have 4 factors; interaction, involvement, quality and intimacy. All these 4 items of social networking sites and items of social solidarity will be measured to the respondents. As for this research is to determine the level of social networking sites (SNS) among users, to identify the level of social solidarity among users and to determine the relationship between social networking sites (SNS) and social solidarity.